Hermann Togo - Ouahigouya (Yatenga province), Burkina Faso - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Hermann Togo, a social worker in charge of CEF the "Conseil Á  l'Exploitation Familiale" (Advise for Family Enterprises), a farmers' union, talks about how they help farmers make informed decisions, and adapt to changes in the climate. One way the union has helped the farmers is through the farmer's own radio 'La Voix du Paysan' (The voice of the farmer). This communication tool allows the farmers to quickly disseminate simplified information about new techniques over a large area.